Sistem Pengajuan Penerbitan Seafarers Identity Document (SID) Pada Direktorat Perkapalan Dan Kepelautan - Annas, Hafizh; inting, Dafid G (Innovative: Journal Of Social Science Research, 2023)
The preparation of this paper or research was carried out with the aim and objective of finding out the application system for issuing seafarers identity documents (SID) to the Directorate of Shipping and Maritime Affairs. The author obtained data using field research methods and library research methods. The Directorate of Shipping and Maritime Affairs is a part of the Directorate General of Sea Transportation within the Ministry of Transportation of the Republic of Indonesia, where there are five Sub-Directorates and one Sub-Section which have their respective duties and functions. The discussion presented in this paper refers to the services provided by one of the Sub-Directorates, namely the Maritime Affairs Sub-Directorate. This service is a Seafarers Identity Card / SID (Seafarers Identity Document) Issuance service. The issuance of a seafarer's identity card / SID will provide security and comfort for seafarers who will sail abroad in accordance with the standards of the convention that has been ratified by Indonesia. Historically, Indonesia ratified the Seafarer's Identity Card on January 4 2008. However, the Directorate of Shipping and Maritime Affairs in issuing the Seafarer's Identity Card has not been implemented efficiently. This is due to the lack of available facilities so that they cannot keep up with the surge in SID issuance applicants. Based on the published Circular, the Seafarer's Identity Card / SID Issuance process begins by registering via the website https://e-SID.dephub.go.id, then you will receive confirmation of the SID issuance application schedule by coming directly to the SID Issuance room to collect biometric data as well as bringing the SID requirement documents for the One-Stop Integrated Service (PTSA) at the Ministry of Transportation of the Republic of Indonesia.